A Study Of The Problematic Tradition And Modernity In Islamic Thought Based On A Contemporary Approach - Rouf, Abdul Mukti (Millati: Journal of Islamic Studies and Humanities, 2024)
This study is primarily concerned with the challenges posed by the Arab-Islamic revival and its relationship to the system of reason that is intrinsic to the Arab-Islamic tradition of thought. The object of this study can be traced through the dialectics of contemporary Islamic thought, as evidenced in the tenets of several dominant madhabs, including those espoused by fundamentalists, liberalists, Marxists and post-traditionalists. The data is studied and analysed through the lenses of hermeneutics and the sociology of knowledge. This study finds that one of the causes of the decline and stagnation of the revival of Islamic civilisation in terms of its epistemology is the unduly strong Arab-Islamic system of thought, which relies on the glory of the past without a critical reading of the past itself and of modernity as an achievement of Western civilisation.